Clinical application of thoracic paravertebral anesthetic block in breast surgeries - Faria,Sara Socorro (2015)
INTRODUCTION: Optimum treatment for postoperative pain has been of fundamental importance in surgical patient care. Among the analgesic techniques aimed at this group of patients, thoracic paravertebral block combined with general anesthesia stands out for the good results and favorable risk-benefit ratio. Many local anesthetics and other adjuvant drugs are being investigated for use in this technique, in order to improve the quality of analgesia and reduce adverse effects. OBJECTIVE: Evaluate the effectiveness and safety of paravertebral block compared to other analgesic and anesthetic regimens in women undergoing breast cancer surgeries. METHODS: Integrative literature review from 1966 to 2012, using specific terms in computerized databases of articles investigating the clinical characteristics, adverse effects, and beneficial effects of thoracic paravertebral block. RESULTS: On the selected date, 16 randomized studies that met the selection criteria established for this literature review were identified. Thoracic paravertebral block showed a significant reduction of postoperative pain, as well as decreased pain during arm movement after surgery. CONCLUSION: Thoracic paravertebral block reduced postoperative analgesic requirement compared to placebo group, markedly within the first 24 h. The use of this technique could ensure postoperative analgesia of clinical relevance. Further studies with larger populations are necessary, as paravertebral block seems to be promising for preemptive analgesia in breast cancer surgery.